The Difference In Potassium Levels In Fresh Blood Bags With Blood Bags Stored At Pku Muhammadiyah Gamping Hospital - Suryanto, Suryanto; Muhammad Gugun, Adang; Nurpratami, Diah (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Blood transfusion, one of them, is a process of transferring blood components containing glucose, lactate, and potassium. During storage, blood cells undergo metabolic changes such as decreased blood pH, hemolysis, and increased potassium levels. One of the complications of transfusion that must be avoided is hyperkalemia due to the release of potassium. This study aimed to determine differences in stored blood potassium levels and PRC QC results during 11 days of storage. This was an analytic observational study with a cross sectional approach. A T-test was used to analyze the difference. In addition, PRC blood quality control (QC) was also carried out for stored blood according to standards. This study used 40 samples of fresh blood bags obtained from UTD PMI Yogyakarta City. The mean potassium level in fresh blood bags was 4.373 ± 0.417 mmol/L (3.70-5.50) and the average potassium level in blood bags stored for 6 days was 8.290 ± 0.275 mmol/L (7.80-8.90). There was a significant difference in potassium levels between fresh blood bags and blood bags stored for 6 days (p = 0.000). The overall QC PRC result is 50% which indicates the need for improvement in terms of the blood component separation process.